Verus Israel : Study of the Relations Between Christians and Jews in the Roman Empire, AD 135-425. - Simon, Marcel (Littman Library of Jewish Civilization, The, 1996)
Marcel Simon's classic study examines Jewish-Christian relations in the Roman Empire from the second Jewish War (132-5 CE) to the end of the Jewish Patriarchate in 425 CE. First published in French in 1948, the book overturns the then commonly held view that the Jewish and Christian communities gradually ceased to interact and that the Jews gave up proselytizing among the gentiles. On the contrary, Simon maintains that Judaism continued to make its influence felt on the world at large and to be influenced by it in turn. He analyses both the antagonisms and the attractions between the two faith.